A systematic review of the international prevalence of BRCA mutation in breast cancer - Armstrong, Nigel; Ryder, Steve; Forbes, Carol; Ross, Janine; Quek, Ruben GW (Clinical epidemiology, 2019)
A systematic review was conducted, summarizing international or ( ) mutation prevalence in breast cancer. Databases (eg, Medline and Embase; N=7) and conferences were searched (January 2012 to December 2017). From 17,872 records, 70 studies were included. In 58 large (N>100) studies, mutation prevalence varied widely from 1.8% (Spain) in sporadic breast cancer to 36.9% (United States) in estrogen receptor/progesterone receptor low+ (1-9% on immunohistochemistry/human epidermal growth factor receptor 2-negative [HER2-]) breast cancer. In 2 large studies unselected for family history, ethnicity, sex, or age and no/unclear selection by breast cancer stage or hormone receptor (HR) status, germline (g ) mutation prevalence was 2.9% (Italy) to 3.0% (South Korea). In the 4 large unselected triple-negative breast cancer studies, g mutation prevalence varied from 9.3% (Australia) to 15.4% (United States). g mutation prevalence in 1 large unselected HR positive/HER2- early breast cancer study was 5% (United States). In 2 large unselected metastatic breast cancer studies, g mutation prevalence was 2.7% (France) and 4.3% (Germany). Locally advanced breast cancer studies were small and not in unselected populations. Poor reporting of g status and basis of selection implies a need for further large well-reported mutation prevalence studies in breast cancer.